2007
DOI: 10.1007/s00127-007-0229-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mental illness on patient satisfaction with the therapeutic relationship

Abstract: Patients' perceptions of the therapeutic relationship may be influenced by psychopathology. Teams comprising many patients with severe mental illness may constrain the therapeutic relationship. Hence, resources and organizational measures should be carefully considered in such care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 31 publications
2
26
1
Order By: Relevance
“…Whether the consulting room is private This study found that being female increases a user's chance of being satisfied by 17% compared to being male, which was consistent with other studies 18,19,20 . This association may be because the woman's health was a priority action and some studies claim that health services are mostly frequented by women, particularly within the FHS 21,22,23,24 .…”
supporting
confidence: 91%
“…Whether the consulting room is private This study found that being female increases a user's chance of being satisfied by 17% compared to being male, which was consistent with other studies 18,19,20 . This association may be because the woman's health was a priority action and some studies claim that health services are mostly frequented by women, particularly within the FHS 21,22,23,24 .…”
supporting
confidence: 91%
“…Patient satisfaction assessment is considered the cornerstone care outcome measure, and the key indicator of service quality and treatment evaluations [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…More satisfied patients have better health outcomes after hospital discharge,16 which reduces the likelihood of rehospitalization 14. Understanding the determinants of satisfaction is of importance when developing effective interventions that can improve patient satisfaction, which may, in turn, improve other health-related outcomes and reduce rehospitalization 17–19…”
Section: Introductionmentioning
confidence: 99%